Relation between dental fluorosis and intelligence quotient in school children of Bagalkot district - P K Shivaprakash; Kushagra Ohri; Hina Noorani (Wolters Kluwer Medknow Publications, 2011)
This study was conducted on 160 children, in the Bagalkot district of Karnataka state between August and October 2010, with the aim of finding out if there is a relation between dental fluorosis status and Intelligence Quotient (IQ). Children were categorized as, those suffering from dental fluorosis and those not suffering from dental fluorosis and for all children in both categories, Intelligence testing was done using the Raven's Coloured Progressive Matrices. The following observations were made from the data gathered: The mean IQ score of children without dental fluorosis was significantly higher than those children who had dental fluorosis. The mean IQ scores did not vary with the severity of dental fluorosis as classified by Dean's fluorosis index. Also it was noticed that the percentage of children with dental fluorosis was more in Extremely Low and Low IQ categories whereas the percentage of children without dental fluorosis was more in Average and High Average IQ categories. Previous studies had indicated toward decreased Intelligence in children exposed to high levels of fluoride and our study also confirmed such an effect.